2023
DOI: 10.1002/clt2.12248
|View full text |Cite
|
Sign up to set email alerts
|

The use of patient‐reported outcome measures by healthcare professionals in specialized asthma management centers in French‐speaking Belgium: A mixed‐methods study

Abstract: Introduction Recently, the literature has promoted the use of patient‐reported outcome measures (PROMs) in clinical practice as a means to foster patient engagement. However, conditions necessary to support the use of PROMs to encourage asthma patient engagement are not clearly defined. Therefore, we sought (1) to explore the current and ideal use of PROMs by healthcare professionals (HP) in specialized asthma management centers in French‐speaking Belgium and (2) to understand under which conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Overall, higher levels of agreement among patients, family caregivers and healthcare providers on why they completed the PROMs underline the importance of educating these three groups about patient-reported measures like PROM. Some recent studies have shown that using PROMs have the potential to transform current model of clinically focused and utilitarian model of patient care 6 17. Similarly, higher levels of agreement on the helpfulness of the user guides show that health systems need to create resources like user guides for patients, family caregivers and healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, higher levels of agreement among patients, family caregivers and healthcare providers on why they completed the PROMs underline the importance of educating these three groups about patient-reported measures like PROM. Some recent studies have shown that using PROMs have the potential to transform current model of clinically focused and utilitarian model of patient care 6 17. Similarly, higher levels of agreement on the helpfulness of the user guides show that health systems need to create resources like user guides for patients, family caregivers and healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-reported outcome measures (PROMs) are increasingly being used to provide patient- and family-centred care 1 2. The use of PROMs in routine clinical care has shown to enhance communication between patients, family caregivers and healthcare providers, facilitating patient engagement and discussion on patient- and family-identified concerns, resulting in shared-decision making and attaining better health outcomes for patients 3–6. Despite the growing use of PROMs in the adult population, their implementation in routine paediatric clinical care is still limited 7 8…”
Section: Introductionmentioning
confidence: 99%
“…PROMs have been introduced as tools to standardize patient outcomes by supporting and directing individualized management plans. 17 , 18 We successfully incorporated these into the OLD program, along with inhaler use education, referrals to pulmonary rehabilitation and tobacco cessation. Various studies demonstrate the advantages of this.…”
Section: Discussionmentioning
confidence: 99%